2006
DOI: 10.1002/polb.20958
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence resonance energy transfer by quencher adsorption into hydrogels containing fluorophores

Abstract: We synthesized anionic hydrogels containing fluorophores and investigated the adsorption of a cationic quencher having an amino group into hydrogels by fluorescence resonance energy transfer (FRET). FRET from the fluorophore to the quencher in hydrogels was examined by fluorescence intensity and fluorescence decay using a fluorescence spectrophotometer and femtosecond laser spectroscopy. The fluorescence intensity of the fluorophore-containing hydrogels decreased rapidly with increasing amounts of adsorbed cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Either it can be used to introduce a cross-linker subsequent to the polymerization step or it can act as an anchor for covalent attachment of biologically active ingredients within the preformed gel network. There are also examples where reactive monomers have been pretransformed into biologically significant new monomers that upon polymerization create polymeric hydrogels. For example, therapeutic hydrogels comprised of pamidronate drugs have been prepared by copolymerizing pamidronate acrylate developed from NHSA with NIPAM using a bis­(acrylamide) cross-linker (Scheme a) . Molecules containing bisphosphonate groups can effectively chelate calcium ions and thus can be used as active drugs for curing several bone diseases.…”
Section: Functional Materials By Postpolymerization Modificationmentioning
confidence: 99%
“…Either it can be used to introduce a cross-linker subsequent to the polymerization step or it can act as an anchor for covalent attachment of biologically active ingredients within the preformed gel network. There are also examples where reactive monomers have been pretransformed into biologically significant new monomers that upon polymerization create polymeric hydrogels. For example, therapeutic hydrogels comprised of pamidronate drugs have been prepared by copolymerizing pamidronate acrylate developed from NHSA with NIPAM using a bis­(acrylamide) cross-linker (Scheme a) . Molecules containing bisphosphonate groups can effectively chelate calcium ions and thus can be used as active drugs for curing several bone diseases.…”
Section: Functional Materials By Postpolymerization Modificationmentioning
confidence: 99%
“…4, it can be found that after CdTe QDs were added into C-CPA solution, the integrated area of the fluorescence emission peak of C-CPA with the same concentration declined linearly based on the quantity of CdTe QDs adding into the blending system. The reason is that C-CPA and CdTe QDs formed a D-A pair which based on the dipolar interaction in the blending system 23 . When C-CPA works as the energy donor and CdTe QDs works as the energy accepter, the degree of energy transfer between these two compounds will increase along with the quantity increasing and this made the fluorescence intensity of C-CPA declined linearly with the quantum increase of CdTe QDs.…”
Section: Resultsmentioning
confidence: 99%
“…From the experiments, it was inferred that the contents of coumarin and positive charges on the polymer were the main factors which affected the photoluminescence properties of CdTe QDs. The energy transfer between C-CPA and CdTe QDs followed the fluorescence resonance energy transfer theory (FRET) 23,25,26 , the formula (2) shows the factors which affect the rate constant of FRET:…”
Section: Resultsmentioning
confidence: 99%
“…91 Furthermore, the measurement of fluorescence intensity changes induced by FRET revealed adsorption phenomena related to solutes in the polymer network on a nano-scale level. Acrylate monomer containing 5-(2¢-aminoethyl)aminonaphthalene-1-sulfonic acid (EDANS), a common fluorophore, was synthesized by the coupling of EDANS with N-succinimidylacrylate and the resultant monomer was copolymerized with AAc and MBAA as a crosslinker.…”
Section: Afp-imprinted Hydrogelmentioning
confidence: 99%